LEGAL FORCE AND IMPLICATIONS OF POLITICAL PARTY COURT DECISIONS ON THE SETTLEMENT OF INTERNAL DISPUTES AND INTRAPARTY DEMOCRACY IN INDONESIA - Imran; Taufik Firmanto; Erham (Awang Long Law Review, 2026)
The Political Party Court is an internal institution established by political parties to independently resolve disputes within the party before resorting to state courts. It plays a strategic role in maintaining organizational stability and strengthening intra-party democracy. The objective of this study is to analyze the binding force of the Political Party Court's decisions and their implications for the effectiveness of dispute resolution and the quality of internal party democracy in Indonesia. The research method used is normative legal research with a legislative and conceptual approach based on literature studies. The results of the study indicate that normatively, the decisions of the Party Court are binding on members and administrators based on positive law and the party's Articles of Association/Bylaws, but their effectiveness is often hampered by non-compliance by the parties, weak internal enforcement, and continued open access to state justice. This condition causes the Party Court's function as an autonomous forum for dispute resolution and a driver of transparent and accountable intra-party democracy to not function optimally. Therefore, institutional strengthening, affirmation of the legal standing of its decisions, and increased internal party commitment are needed to make the Party Court the primary mechanism for resolving internal disputes.